Aerobic stability in tropical forage silages treated with Lactobacillus buchneri (Research, Society and Development, 2020)
The ensiling technique is a way of preserving forage by preserving the food in an acidic and oxygen-free environment. Some forage plants, despite having desirable characteristics for ensiling, may have predisposing factors to low aerobic stability. Thus, the objective of this work is to talk about the effects of using Lactobacillus buchneri as an alternative to control the aerobic deterioration of silages of the main tropical forage used in Brazil. Grasses such as sugarcane, corn and sorghum are examples of forages that present problems related to aerobic stability, since they have high concentrations of residual soluble carbohydrates and lactic acid after the active fermentation phase. In order to reduce the losses that may occur in the aerobic phase (after opening the silo), it is possible to use a microbial inoculant (L. buchneri), a heterofermentative bacterial strain that produces lactic acid and also acetic acid, the latter has antifungal characteristics that acts by inhibiting the growth of undesirable microorganisms (yeasts and filamentous fungi) and improving the aerobic stability of silages. The use of Lactobacillus buchneri during the ensiling process reduces losses after opening the silo, as well as improving the sanitary quality of silages due to inhibiting the growth of deteriorating microorganisms.